Protective effects of Lavandula stoechas L. methanol extract against 6-OHDA-induced apoptosis in PC12 cells. (12th June 2021) - Tayarani-Najaran, Zahra; Hadipour, Elham; Seyed Mousavi, Seyed Mahdi; Emami, Seyed Ahmad; Mohtashami, Leila; Javadi, Behjat
Abstract: Ethnopharmacological relevance: Parkinson's disease (PD) is a neurodegenerative disorder associated with oxidative stress-induced neuronal damage and death. In European and Persian Traditional Medicine, aerial parts (leaves, stems, and flowers) of Lavandula stoechas L. have been widely used for treating neurodegenerative disorders including PD. Aim of the study: Herein, the protective effects of L. stoechas methanol extract were investigated on 6-hydroxydopamine (6-OHDA)-induced cytotoxicity and oxidative damage in PC12 cells. Materials and methods: The cells were pretreated with a standardized L. stoechas methanol extract (2.5–20 μg/mL) for 24 h and exposed to 6-OHDA (200 μM) thereafter. The cell viability percentage was determined by AlamarBlue test. Intracellular reactive oxygen species (ROS) production was determined by a fluorimetric method using 2′, 7′-dichlorodihydrofluorescein diacetate and cellular apoptosis was assessed by the fluorescent probe propidium iodide test. Finally, the expression of proteins involved in apoptosis pathway (Phospho SAPK/JNK, SAPK/JNK, p44/42 MAPK (ERK1/2) and Poly ADP ribose polymerase (PARP)) was measured via Western blot analysis. Results: Treatment of PC12 cells with 6-OHDA could significantly increase cytotoxicity, ROS level, and cell apoptosis. Pretreatment of PC12 cells with the extract could significantly decrease 6-OHDA cytotoxicity, ROS production, (2.5 and 5 μg/mL) and cell apoptosis (5 μg/mL). Western blot analysis showed that 6-OHDA exposure could increase the expression of proteins involved in apoptosis signaling, while pretreatment with L. stoechas (5 μg/mL) reduced apoptotic proteins. Conclusions: The present study demonstrated that L. stoechas, which has been traditionally used in Persian Medicine for treating CNS diseases, is a valuable source of active compounds with neuroprotective, anti-oxidant, and anti-apoptotic activity. Graphical abstract: Image 1